Somatic experiencing® for patients with low back pain and comorbid posttraumatic stress disorder - protocol of a randomized controlled trial - Tonny Elmose Andersen; Hanne Ellegaard; Berit Schiøttz-Christensen; Claus Manniche (BMC, 2018)
Abstract Background Research has almost exclusively focused on the neck in order to explain the mechanisms of persistent pain after motor vehicle collisions (MVC). However, studies have shown that low back pain after MVC is as common as neck pain. Also, posttraumatic stress disorder (PTSD) is common after MVCs, and evidence indicate that PTSD may be linked to the development of pain and disability. PTSD has even been proposed as "the missing link" for some in the development of chronic low back pain. Unfortunately, PTSD often goes unattended in low back pain rehabilitation and very few randomized controlled studies exists targeting both conditions. Hence, the aim of the present study is to investigate the potential additional effect of the trauma therapy "Somatic Experiencing®" (SE) in addition to physiotherapy (PT) compared to PT alone for patients with chronic low back pain and comorbid PTSD. Methods The study is a two-group randomized controlled clinical trial in which participants (n = 140) are recruited consecutively from a large Danish spine center in the Region of Southern Denmark, between January 2016 and December 2017. Patients are randomly allocated to one of the two conditions: SE + PT or PT alone. Measurements of effect are carried out at baseline before randomization, post-intervention, 6 and 12 months post-randomization. The primary outcome is a 20% reduction in disability (Rolland Morris Disability Questionnaire) at 6 months post-randomization. Secondary outcomes are: PTSD symptoms, pain intensity, pain-catastrophizing, fear of movement, anxiety and depression. Discussion Comorbid PTSD is currently not targeted in back pain rehabilitation although highly prevalent. If the SE intervention shows to have an additional effect on disability and pain, the study is likely to have a positive impact on the management of chronic low back pain and will have immediate clinical applicability. Trial registration Current Controlled Trials Registration August 4, 2017: NCT03244046. Retrospectively registered.